Statistical analysis and evaluation of stigmatization in a managerial environment - Büngers, Nadja (2022)
The concept of mental health is not accepted universally in our society and, accordingly, does not enjoy the same attention as physical health. People suffering from a mental illness not only have to cope with their symptoms, they face prejudices, wrong stereotypes and stigma regularly. Hence, one intention should be to set an end to stigma, also within the working context. Especially during the ongoing Covid19-pandemic our health and the well-being of the people we care about is a matter of daily concern. The threat to our physical health is immense; nevertheless, due to lockdowns, minimization of social contacts and recommendations to stay home, we are further reminded that a good health itself is characterized not only by physical health, but also by our mental health. The aim of this dissertation is to clarify the process of stigma of mental illnesses and create awareness about it as understanding the concept of stigma is a prerequisite to decide on strategies for its reduction. The findings of this study illustrate that stigma is impacted by the causal attribution of illness; humans tend to make more stigmatizing judgments when an illness is a mental illness that is attributed to mind compared to an illness that is physical and attributed to the body. Furthermore, this research found that mere information about mental illness issues is not a sufficient way to reduce stigma which leads to the proposal of seminars and workshops within a managerial context to educate employees about stigma and reduce it.